2019
DOI: 10.1371/journal.pone.0220377
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of troxerutin on metabolic disorders in non-obese model of metabolic syndrome

Abstract: Background Troxerutin (TRX) has a beneficial effect on blood viscosity and platelet aggregation, and is currently used for the treatment of chronic varicosity. Recently, TRX can improve lipid abnormalities, glucose intolerance and oxidative stress in high-fat diet-induced metabolic disorders. In this study, we tested the effect of TRX on metabolic syndrome-associated disorders using a non-obese model of metabolic syndrome–the Hereditary Hypertriglyceridaemic rats (HHTg). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…To determine the antioxidant effect of cerium oxide-decorated magnetic particles, a strain of HHTg rats was deemed the most suitable experimental model given its tendency to exhibit increased oxidative stress in tissues (Malinska et al, 2019 ). We examined the tissues of the liver, kidney cortex, and brain, where metabolic disorders and changes are associated with metabolic syndrome and diabetes, after administering each nanoparticle type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the antioxidant effect of cerium oxide-decorated magnetic particles, a strain of HHTg rats was deemed the most suitable experimental model given its tendency to exhibit increased oxidative stress in tissues (Malinska et al, 2019 ). We examined the tissues of the liver, kidney cortex, and brain, where metabolic disorders and changes are associated with metabolic syndrome and diabetes, after administering each nanoparticle type.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this report was to merge both the magnetic and antioxidant properties of the maghemite core and cerium oxide shell into a new delivery system that would be colloidally stable and magnetically manipulable. Antioxidant properties were verified based on chemical and biological in vivo tests of using a rat model of metabolic syndrome and prediabetes—the hereditary hypertriglyceridaemic rat (Malinska et al, 2019 ). Effect of cerium oxide-decorated γ-Fe 2 O 3 nanoparticles on oxidative stress and antioxidant defense parameters has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…On its side, the rutin derivate, troxerutin (TRX), has also demonstrated effectiveness against metabolic disorders in a rat model of hereditary hypertriglyceridemia (HHTg) non-obese model of MetS [ 256 ]. The treatment with TRX lowered the levels of hepatic cholesterol and reduced the expression of cholesterol and lipid synthesis genes ( Hydroxymethylglutaryl-CoA reductase ( Hmgcr), Srebp2 and Scd1 ) as well as decreased lipoperoxidation and increased the activity of antioxidant enzymes [ 256 ]. Moreover, these animals exhibited higher levels of adiponectin in serum [ 256 ].…”
Section: Flavonolsmentioning
confidence: 99%
“…In addition, troxerutin has been shown to be effective in the treatment of hemorrhoidal diseases where it protects the endothelial cells and improves local microcirculation [ 10 , 21 ]. In a previous study, 15 DEGs were identified by transcriptomic analysis of the blood cells of rats treated with troxerutin [ 8 ]; this demonstrated that troxerutin mainly possesses functions of T-cell-mediated cytotoxicity, telencephalon development, cell membrane development, endoplasmic reticulum exports, β 2-microglobule binding, and transporter associated with antigen presentation (TAP)-binding. Cerebroprotein hydrolysate, also known as Cerebrolysin [ 22 ], is suggested to play a role as the precursor to a neurotransmitter; it also directly functions as a neurotransmitter and is used to improve the recovery of neurological function [ 9 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Troxerutin, also known as vitamin P4, has been proven to possess antihyperlipidemic, anti-inflammatory, antioxidant, and neuroprotective properties [8]. Cerebroprotein hydrolysate, an affluent of peptides and amino acids [9], has been found to have a synergistic effect, along with troxerutin, due to its ability to pass through the blood-brain barrier easily.…”
Section: Introductionmentioning
confidence: 99%